Cluster-network interaction as a management tool for health tourism market in a regional economy - Матвей Оборин (Вестник Пермского университета: Серия Экономика)
Introduction. Global trends unfolding at various constituent’s levels transform the approaches to economic development management and business adaptation to external challenges. The prerequisites of cluster-network interaction as a special kind of management in various industries originate from a rigorous implementation rate of digital solutions, technological changes, and the need to preserve competitive advantages. At the level of public administration, the cluster-network approach contributes to more efficient regulation and coordination of the functions of business entities, their reasonable integration into the socio-economic system of the regions. The high quality of cluster-network interaction can provide a positive response for related organizations, while this response could also affect local consumer markets and saturate them with valuable products and services. Health tourism is characterized with a complicated industrial algorithm that requires not only the coordination of resource, infrastructure, and human resources, but also proper equipment and facilities for effective diagnostic, wellness, and rehabilitation procedures. Purpose. The purpose of the study is to develop a model of cluster-network interaction in the field of health tourism. Materials and Methods. Methodologically, the work refers to the scientific and theoretical theories of clusters, networks, cluster-network interactions among a wide range of agents with various functions and capacities. Scientific, theoretical, and statistical analysis, modeling of cluster-network interaction are the key research methods. The official Rosstat data about tourism and health services were the information resources for the study. Results. The author of the study analyzed approaches to the description of economic and market processes driven by cluster-network interaction and defined the levels and key agents of its application. The study also systematized the conditions and factors for cluster-network units specialized in medical and wellness services. Conclusions. The author developed a cluster-network interaction model for managing health tourism market. The proposed model is tailored to the peculiarities of spatial and territorial location and the market potential of the country’s resort medicine.